2006
DOI: 10.1152/ajpheart.00648.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increased ventricular repolarization heterogeneity in patients with ventricular arrhythmia vulnerability and cardiomyopathy: a human in vivo study

Abstract: Increased repolarization heterogeneity can provide the substrate for reentrant ventricular arrhythmias in animal models of cardiomyopathy. We hypothesized that ventricular repolarization heterogeneity is also greater in patients with cardiomyopathy and ventricular arrhythmia vulnerability (inducible ventricular tachycardia or positive microvolt T wave alternans, VT/TWA) compared with a similar patient population without ventricular arrhythmia vulnerability (no VT/TWA). Endocardial and epicardial repolarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 40 publications
8
53
1
1
Order By: Relevance
“…In the human heart, no transmural gradients in ARIs 20 or repolarization times 21 (ie, the sum of activation time and ARI) were found and an analysis of the data from Franz et al 22 showed that epicardial repolarization occurred later than endocardial repolarization. 23 In the study of Chauhan et al, 24 repolarization time in the anteroseptal right ventricular endocardium in cardiomyopathy patients without arrhythmias was on average 288 ms, and left ventricular epicardial repolarization time adjacent to the septum was 287 ms.…”
Section: Response By Patel Et Al P 96mentioning
confidence: 95%
“…In the human heart, no transmural gradients in ARIs 20 or repolarization times 21 (ie, the sum of activation time and ARI) were found and an analysis of the data from Franz et al 22 showed that epicardial repolarization occurred later than endocardial repolarization. 23 In the study of Chauhan et al, 24 repolarization time in the anteroseptal right ventricular endocardium in cardiomyopathy patients without arrhythmias was on average 288 ms, and left ventricular epicardial repolarization time adjacent to the septum was 287 ms.…”
Section: Response By Patel Et Al P 96mentioning
confidence: 95%
“…Methods to estimate t d and w 1 can be found in [34], [35]. This approximated modeling to derive the T wave can be adapted to situations with increased dispersion of the RT s, as it happens in patients with increased vulnerability to ventricular arrhythmias [36]. In that case, the second order contribution in (6) becomes relevant and the following secondorder approximation of (4) can be used:…”
Section: Biophysical Modeling Of the Ecgmentioning
confidence: 99%
“…T6 T5 T3 T2 T1 T4 T7 T8 T6 T5 T3 T2 T1 T4 I II V6 V5 V3 V2 V1 V4 8 In order to obtain a suitable transformation matrix Υ the average ST-T complexes are canceled out by subtracting the previous complex from each complex x i,l = x i,l − x i−1,l . These detrended beats x i,l are used to build the matrices X and X (m) as in (35) and (36). Note that X and X (m) now contain K − 1 beats.…”
Section: Ecg Markers For Characterization Of Spatio-temporal Repolmentioning
confidence: 99%
“…49 In addition to fibrosis, other factors, such as altered expression and distribution of connexin proteins and increased sympathetic activity, can further enhance the susceptibility to arrhythmias in DCM patients. 50,51 Poor cell-to-cell coupling promotes regions of conduction slowing, leading to functional and anatomic conduction block and causing reentrant excitation. In some scar regions an isthmus of slow conduction may have a complex 3-dimensional path for propagation within and/or across all 3 myocardial layers that causes sustained VT. 52 Much of our understanding of SMVT in DCM comes from studies of mapping and ablation in which scar is detected from evidence of low voltage (<1.5 mV in bipolar recordings) and abnormal electrograms.…”
Section: Electrophysiologic Substrate For Ventricular Tachycardia In mentioning
confidence: 99%